Design, synthesis and in silico prediction of drug-likeness properties of new ortho, meta and para-(2-cyano-3-(3,5-di-tert-butyl-4- hydroxyphenyl)acrylamido)benzoic acids - Madhavi Kuchana, Lakshmi Bhavani Kambala (Journal of Applied Pharmaceutical Science, 2021)
Entacapone clinically used as an anti-parkinsonian drug possess substituted 2-cyano-3-phenylacrylamide structure. Some anti-inflammatory drugs contain 3,5-di-tert-butyl-4-hydroxyphenyl moiety and few other drugs contain aminobenzoic acid moiety in their structure. The therapeutic activity of these drugs was attributed to the specified structural features. In view of this, the present study aimed to design and synthesize new ortho, meta and para- (2-cyano-3-(3,5-di-tert-butyl-4-hydroxyphenyl)acrylamido)benzoic acids which contain the above specified active structural units. The study also aimed to perform in silico prediction of drug-likeness properties and bioactivity. The title compounds were synthesized by knoevenagel condensation of cyanoacetyl aminobenzoic acids with 3,5-di-tertbutyl-4-hydroxybenzaldehyde. The synthesized products were purified and characterized by physical and spectral methods. The in silico prediction of drug-likeness properties and bioactivity was carried out for the designed and synthesized title compounds as well as cyanoacetyl aminobenzoic acids through online software Molinspiration Cheminformatics. The in silico prediction indicated that all the compounds obeyed Lipinski’s rule and the title compounds were active as Nuclear receptor ligands. Therefore, the present study concluded that the compounds having 2-cyano-3-phenylacrylamide structure with 3,5-di-tert-butyl-4-hydroxy group over phenyl ring and benzoic acid moiety on nitrogen atom were essential for drug-likeness properties and bioactivity as Nuclear receptor ligands.
Keywords: 2-cyano-3-phenylacrylamide, aminobenzoic acids, 3,5-ditert-butyl-4-hydroxyphenyl derivatives, Lipinski’s rule.